The role of a clinician amid the rise of mobile health technology. (2nd August 2019) - Yang, William E; Shah, Lochan M; Spaulding, Erin M; Wang, Jane; Xun, Helen; Weng, Daniel; Shan, Rongzi; Wongvibulsin, Shannon; Marvel, Francoise A; Martin, Seth S
Abstract: Mobile health (mHealth) interventions have demonstrated promise in improving outcomes by motivating patients to adopt and maintain healthy lifestyle changes as well as improve adherence to guideline-directed medical therapy. Early results combining behavioral economic strategies with mHealth delivery have demonstrated mixed results. In reviewing these studies, we propose that the success of a mHealth intervention links more strongly with how well it connects patients back to routine clinical care, rather than its behavior modification technique in isolation. This underscores the critical role of clinician-patient partnerships in the design and delivery of such interventions, while also raising important questions regarding long-term sustainability and scalability. Further exploration of our hypothesis may increase opportunities for multidisciplinary clinical teams to connect with and engage patients using mHealth technologies in unprecedented ways.